Grounding and shielding for the high-voltage laboratory / Mohd. Yusry Baharudin - Baharudin, Mohd. Yusry (1995)
This report describes the grounding system for a high-voltage laboratory. The report also contain the proposed layout for the high-voltage lab. The layout consist of the arrangement of the equipments, clearances and shielding of the laboratory in the Electrical Engineering Department of ITM. The existing grounding system is insufficient and also the route of the grounding electrodes is not known. In this project, efforts have been made to determine the location of grounding electrodes by making use of the earth's electric field nearby the suspected electrode's location and its nearby. Several data are obtained and then have been compared so as to determine the exact location. The potential gradient at that point is expected to be higher than its surrounding which is due to the existence of the electrode (or charged object) at that point.